1992
DOI: 10.1002/ana.410320305
|View full text |Cite
|
Sign up to set email alerts
|

Myelin basic protein–specific T lymphocytes in multiple sclerosis and controls: Precursor frequency, fine specificity, and cytotoxicity

Abstract: A panel of 90 myelin basic protein (MBP)-specific T-cell lines were derived from peripheral blood of eight patients with multiple sclerosis and four normal subjects. The precursor frequency of MBP-reactive T cells in peripheral blood mononuclear cells ranged from 10(-7) to 9 x 10(-7) (mean, 6.7 x 10(-7)) in the group of patients with multiple sclerosis and from 0.5 x 10(-7) to 9.8 x 10(-7) (mean, 5.6 x 10(-7)) in the control subjects. This difference between the two groups was not statistically significant (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(46 citation statements)
references
References 37 publications
6
40
0
Order By: Relevance
“…We cannot exclude that ongoing autoantigen-driven T cell proliferation associated with acute MS relapses primarily impairs the TREC content of peripheral lymphocytes. However, autoreactive T cells represent a minor portion within the peripheral T cell repertoire (26,27), and it is unlikely that an increased turnover of autoaggressive T cell clones alone mediates such a pronounced reduction of circulating TRECexpressing T cells in patients with early stage MS. In our study population, the TREC content was not influenced by the frequency or severity of prior relapses, and even patients with extremely low TREC numbers in PBLs (Ͻ1 ϫ 10 3 /10 6 cells) did not differ from the remaining study population with respect to disease duration, relapse rate, and disability, as determined by the expanded disability status scale (28).…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude that ongoing autoantigen-driven T cell proliferation associated with acute MS relapses primarily impairs the TREC content of peripheral lymphocytes. However, autoreactive T cells represent a minor portion within the peripheral T cell repertoire (26,27), and it is unlikely that an increased turnover of autoaggressive T cell clones alone mediates such a pronounced reduction of circulating TRECexpressing T cells in patients with early stage MS. In our study population, the TREC content was not influenced by the frequency or severity of prior relapses, and even patients with extremely low TREC numbers in PBLs (Ͻ1 ϫ 10 3 /10 6 cells) did not differ from the remaining study population with respect to disease duration, relapse rate, and disability, as determined by the expanded disability status scale (28).…”
Section: Discussionmentioning
confidence: 99%
“…Autoreactive T cells regularly escape into the periphery. This includes CD4 ϩ T cells specific for myelin Ags, the mediators of experimental autoimmune encephalomyelitis (EAE) 3 and presumably of multiple sclerosis (MS) (1)(2)(3)(4)(5)(6). Furthermore, candidate autoantigens, including isoforms of myelin basic protein and proteolipid protein (PLP), have been detected in secondary lymphoid tissues, where they might be accessible for processing and presentation by professional APCs (7)(8)(9)(10)(11)(12).…”
Section: Activation Of Apcsmentioning
confidence: 99%
“…In that study, the authors demonstrated that MBP-reactive T cells occurred at a range of 1/300-1/1,000 total T cells in MS patients using oligonucleotide probes and cDNA cloning [24]. The precursor frequency of MBP-reactive T cells as reported by Bieganowska and colleagues [24] is higher than that measured by cell culture-based assay or ELISPOT assay by two to three logs [4,5,10,11,[21][22][23]. The study has raised the important issue that the precursor frequency of MBPreactive T cells is significantly underestimated in MS patients, as well as some confusion as to whether these clonal populations of MBP-reactive T cells truly occur at such high precursor frequency (1/300 total T cells) in MS patients.…”
Section: Introductionmentioning
confidence: 82%
“…Although the etiology and pathogenesis of the disease remain elusive, there is evidence suggesting that the T cell responses to certain myelin autoantigens may play an important role in the disease processes [1]. Among the candidate myelin proteins identified so far that are capable of inducing EAE, myelin basic protein (MBP) has been studied most extensively with respect to the complete profile of the T cell reactivity to various epitopes of the protein in both EAE models and humans [2][3][4][5][6][7]. In humans, there is evidence indicating that MBP-reactive T cells undergo in vivo activation and clonal expansion in MS patients as opposed to control subjects [8][9][10][11] and occur at an increased frequency during clinical exacerbation [12].…”
Section: Introductionmentioning
confidence: 99%